Existential concerns among young adults with psychotic vulnerability in mental health care: a qualitative study in the Netherlands - Marlous L. D. de Vries; Pauline Janse; Christa W. Anbeek; Arjan W. Braam (BMC Psychiatry)
Abstract Background Young adults with psychotic vulnerability are dealing with disrupting experiences early in life, often with far-reaching or even lifelong impacts. These experiences can lead to existential questions during young adulthood. Identity realization and finding meaning and purpose in life are central to this development stage. Aim The current study investigated to what extent profound experiences such as psychosis in young adulthood lead to existential concerns as formulated by Yalom and to other existential themes during inpatient and outpatient mental health treatment and care. Methods A qualitative study was carried out among patients (N = 11) with psychotic vulnerability aged between 17 and 31 years, participating in interviews about their existential life questions and experiences in mental health care. In the thematic analysis, the primary deductive codes were based on theory, while the subcodes were inductively derived from the interviews. Results The respondents clearly affirmed existential concerns about freedom (e.g., loss of or changed future), meaninglessness (e.g., questioning purpose and meaning), isolation (e.g., disconnection, importance of personal bonds), identity (e.g., loss of self, changed identity) and death (e.g., questioning life and death). The five existential themes appeared to be related to each other. Furthermore, the importance of addressing existential themes in treatment emerged as a latent care need. Discussion The results of this study provide insight into experiences with meaning-making in mental health care and existential themes. The respondents generally expressed positive feelings about addressing and the possibility to talk about existential life questions, which fits within recovery oriented mental health care.